2019
DOI: 10.1111/mmi.14408
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive pilus production by FCT type 3 Streptococcus pyogenes controlled by Nra regulator translational efficiency

Abstract: Streptococcus pyogenes produces a diverse variety of pili in a serotype-dependent manner and thermosensitive expression of pilus biogenesis genes was previously observed in a serotype M49 strain.However, the precise mechanism and biological significance remain unclear. Herein, the pilus expression analysis revealed the thermosensitive pilus production only in strains possessing the transcriptional regulator Nra. Experimental data obtained for nra deletion and conditional nra-expressing strains in the backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 83 publications
2
17
0
Order By: Relevance
“…Temperature dependent regulation is important in FCT-3 strains. This is primarily governed by post-transcriptional control of nra mRNA translation via a stem loop structure in the coding region ( Nakata et al, 2020 ). The stem loop is positioned proximal to the ribosome border and is considered to be important for promoting translation, although other factors such as its distance from the translation start codon and other mRNA structures around the Shine and Dalgarno sequence may contribute.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Temperature dependent regulation is important in FCT-3 strains. This is primarily governed by post-transcriptional control of nra mRNA translation via a stem loop structure in the coding region ( Nakata et al, 2020 ). The stem loop is positioned proximal to the ribosome border and is considered to be important for promoting translation, although other factors such as its distance from the translation start codon and other mRNA structures around the Shine and Dalgarno sequence may contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that both RofA and Nra can function as autoregulators ( Podbielski et al, 1999 ; Granok et al, 2000 ), and expression of pilus genes in FCT-3 strains is positively or negatively regulated by Nra in a strain-specific manner ( Podbielski et al, 1999 ; Luo et al, 2008 ). Recent studies of in-frame deletion mutants indicated that Nra acts as a positive regulator in several M3 strains and an M49 strain ( Calfee et al, 2018 ; Nakata et al, 2020 ). RofA has been reported to be a positive regulator for the protein F1 gene ( prtF 1) ( Fogg et al, 1994 ).…”
Section: Regulation Of Pilus Gene Expressionmentioning
confidence: 99%
See 3 more Smart Citations